Portfolio effects, climate change, and the persistence of small populations: analyses on the rare plant Saussurea weberi. Issue 4 (20th March 2017) - Abbott, Ronald E.; Doak, Daniel F.; DeMarche, Megan L.
Abstract: The mechanisms that stabilize small populations in the face of environmental variation are crucial to their long‐term persistence. Building from diversity–stability concepts in community ecology, within‐population diversity is gaining attention as an important component of population stability. Genetic and microhabitat variation within populations can generate diverse responses to common environmental fluctuations, dampening temporal variability across the population as a whole through portfolio effects. Yet, the potential for portfolio effects to operate at small scales within populations or to change with systematic environmental shifts, such as climate change, remain largely unexplored. We tracked the abundance of a rare alpine perennial plant, Saussurea weberi, in 49 1‐m 2 plots within a single population over 20 yr. We estimated among‐plot correlations in log annual growth rate to test for population‐level synchrony and quantify portfolio effects across the 20‐yr study period and also in 5‐yr subsets based on June temperature quartiles. Asynchrony among plots, due to different plot‐level responses to June temperature, reduced overall fluctuations in abundance and the probability of decline in population models, even when accounting for the effects of density dependence on dynamics. However, plots became more synchronous and portfolio effects decreased during the warmest years of the study, suggesting that future climate warming may erode stabilizing mechanisms in populations of this rare plant.